2015
DOI: 10.1074/jbc.m114.600312
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Receptor Sumoylation Is Required for Preadipocyte Differentiation and Proliferation

Abstract: Background: Thyroid hormone receptor (TR) sumoylation is essential for thyroid hormone regulation of gene expression. Results: TR sumoylation mutants impair differentiation though down-regulation of C/EBPs, constitutive interaction with NCoR, interference with PPAR␥ signaling, and disruption of the Wnt canonical signaling pathway important for preadipocyte proliferation. Conclusion: TR sumoylation site mutations impair preadipocyte proliferation and differentiation. Significance: TR sumoylation is required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 71 publications
(69 reference statements)
0
17
0
Order By: Relevance
“…SLCO4C1 is a member of the transporter superfamily mediating the transport of thyroid hormones, and ( van der Deure et al 2010 ). It has been shown that when preadipocytes are transduced with an inactive thyroid hormone receptor mutant a decrease in the expression of adipogenic markers is observed ( Liu et al 2015 ). This suggests that increased intracellular thyroid hormone levels, which may be mediated by SLCO4C1, enhance human adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…SLCO4C1 is a member of the transporter superfamily mediating the transport of thyroid hormones, and ( van der Deure et al 2010 ). It has been shown that when preadipocytes are transduced with an inactive thyroid hormone receptor mutant a decrease in the expression of adipogenic markers is observed ( Liu et al 2015 ). This suggests that increased intracellular thyroid hormone levels, which may be mediated by SLCO4C1, enhance human adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…TRs are expressed and functional in ESC/iPSC and we detected a switch from TRα to TRβ during ESC/iPSC differentiation along the hepatocyte lineage in vitro [ 44 ]. Unliganded TRα is also important in preadipocyte differentiation and myoblast proliferation and differentiation [ 79 , 80 ] and early stages of Xenopus metamorphosis [ 23 , 25 , 26 ]. It will be interesting to ask if these effects also involve actions of predominantly cytoplasmic TRα.…”
Section: Discussionmentioning
confidence: 99%
“…The TR isoforms exist in the nucleus both in the presence and absence of TH and the isoforms have separate ligand-independent and dependent actions that appear to be the result of differential recruitment of co-regulatory protein complexes by the TR. In addition to their basic protein structure the TR isoforms can be modified post-translationally including by sumoylation, which may greatly change their function [9]. …”
Section: The Thyroid Hormone Receptor Isoformsmentioning
confidence: 99%